KAJIAN PEMANFAATAN BUANGAN PANAS KONDENSOR AC UNTUK PENGERINGAN PAKAIAN - Utomo, Bawon; Nur Rahmi, Wiwit; Gunawan, Safri (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
The topic of this research is the engineering testing of a clothes drying machine by utilizing the waste heat condenser AC to dry clothes. The purpose of this study is to obtain the temperature and humidity of the average drying air in the drying chamber and to reduce the mass of the clothes to be dried. The heat output from the condenser is directly used to dry clothes on the dryer. The study was conducted within 30 minutes of the drying period. Clothing material used in this study is material with 100% cotton + polyester100% with a wet mass of 0.440 kg and a dry mass of 0.330 kg. The results obtained from this study were obtained mass of dry clothing in the 13th minute with a drying rate of 0.0085kg/s. The conclusion obtained that the use of condenser output for drying clothes is very beneficial for the utilization of wasted condenser heat. Keyword: AC Condensor, drying machine, clothes